Are positive-pressure ventilation lobby rooms effective for protective and source isolation?. Issue 1 (September 2020) - Poovelikunnel, T.T.; Barakat, A.; O'Hara, A.; Humphreys, H.J.; Newmann, V.; Talento, A.F.
SUMMARY: High-efficiency particulate air supplied to a positive-pressure ventilation lobby (PPVL) in isolation rooms offers the dual advantage of protective and source isolation. This study demonstrates the in-use validity of PPVL rooms for protective isolation of patients. Of the 48 PPVL air samples investigated, Aspergillus fumigatus was detected from only one (2%) sample. Local and remote monitoring of the PPVL rooms is essential for the safety of patients and healthcare workers. Remote and point-of-use engineering controls are essential for ongoing ventilation monitoring, but this should be complemented by visual inspection of the isolation suite. Periodic microbiological monitoring should also be considered with other control measures.